Haikyu!! 33, Monster's ball - Furudate, Haruichi, 1983- (Shonen Jump manga., 2019)
"Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? The final points between Karasuno and Inarizaki are tossed back and forth as both teams struggle to finish the other off and declare victory. But with time running out, will Karasuno be able to win the final set, or will Inarizaki send them packing?"--Page 4 of cover.